Loading

Before starting, look whether either equation has common factors. Equation 1 does common factor 2, so divide it by 2 both sides to get 1) 2x - y = 14. Rearrange 1) to get one unknown in terms of the other. In this case, y as follows: 2x = 14 + y, 2x -14 = y. Substitute y in the second equation 2) using y = 2x - 14: 4(2x - 14) -3x = -36,going to 8x - 56 -3x = -36, move numbers to right and simplify x terms on the left: 8x - 3x = 56 - 36 giving 5x = 20 dividing by 5 to get x = 4. Now x = 4 is known, so substitute into the first equation 1) y = 2x - 14 to get y: y = 2(4) -14 going to y = 8 - 14, hence y = -6. Final Answer: x = 4, y = -6